Use of rita® temporary immersion system to obtain microtubers of several mashua Tropaeolum tuberosum Ruiz y Pavón morphotypes - Peña-Rojas Gilmar (2020)
Background. The Temporary Immersion System (TIS) is an effective strategy to obtain quality mashua microtubers through the in vitro propagation of seedlings in a small space and in a short period of time. Objective. Obtain microtubers of 27 mashua morphotypes (Tropaeolum tuberosum) using the TIS-RITA®. Methodology. The seedlings were previously propagated in MS (Murashige & Skoog) solid medium, supplemented with 3% sucrose, at 5.6 pH and 0.7% agar. After fifteen days of cultivation in this medium, the seedlings were transferred to a MS liquid. For the tuberization process, seedlings with an average size of 10 cm were transferred to TIS-RITA® systems for ten weeks, under conditions of complete darkness, at 19 ± 2 ° C, an immersion frequency of 2 minutes every 3 hours in a MS liquid medium supplemented with 8% sucrose and 2 mg.L-1 benzylamino purine (BAP). Results. The best results of microtubers were obtained with different morphotypes, which are respect to i/size, MAC 06A (1.9 cm) and MAC 056 (1.8 cm); ii / fresh weight, MAC 06A (0.2g) and MAC 092 (0.18 g); iii / quantity, MAC 08A (51 units) and MAC 048 (56 units). Implications. TIS-RITA® can be used to obtain quality and virus-free seeds of a wide variety of commercially important crops. Conclusion. The SIT-RITA® based on the intermittent contact of the explants cultivating medium, is an efficient system to obtain mashua microtubers.